Musculotopic organization of the motor neurons supplying the mouse hindlimb muscles: a quantitative study using Fluoro-Gold retrograde tracing - Bacskai, T.; Rusznak, Z.; Paxinos, G.; Watson, Charles (Springer, 2014)
We have mapped the motor neurons (MNs) supplying the major hindlimb muscles of transgenic (C57/BL6J-ChAT-EGFP) and wild-type (C57/BL6J) mice. The fluorescent retrograde tracer Fluoro-Gold was injected into 19 hindlimb muscles. Consecutive transverse spinal cord sections were harvested, the MNs counted, and the MN columns reconstructed in 3D. Three longitudinal MN columns were identified. The dorsolateral column extends from L4 to L6 and consists of MNs innervating the crural muscles and the foot. The ventrolateral column extends from L1 to L6 and accommodates MNs supplying the iliopsoas, gluteal, and quadriceps femoris muscles. The middle part of the ventral horn hosts the central MN column, which extends between L2–L6 and consists of MNs for the thigh adductor, hamstring, and quadratus femoris muscles. Within these longitudinal columns, the arrangement of the different MN groups reflects their somatotopic organization. MNs innervating muscles developing from the dorsal (e.g., quadriceps) and ventral muscle mass (e.g., hamstring) are situated in the lateral and medial part of the ventral gray, respectively.MN pools belonging to proximal muscles (e.g., quadratus femoris and iliopsoas) are situatedventral to those supplying more distal ones (e.g., plantar muscles). Finally, MNs innervatingflexors (e.g., posterior crural muscles) are more medial than those belonging to extensors ofthe same joint (e.g., anterior crural muscles). These data extend and modify the MN maps in the recently published atlas of the mouse spinal cord and may help when assessing neuronal loss associated with MN diseases.